The macroeconomic impact of COVID-19 in Mozambique: A social accounting matrix approach - Rosário Betho; Marcia Chelengo; Sam Jones; Michael Keller; Ibraimo Hassane Mussagy; Dirk van Seventer; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study aims to assess the economic costs of COVID-19 and the state of emergency implemented by the Government of Mozambique, relying on a social accounting matrix. It produces numerical results that represent the direct effect on (or 'shocks' to) the economy associated with the pandemic. We distinguish four channels-supply, demand, investment, and export-by which the state of emergency and other efforts influence economic activity. Our simulation suggests that the Mozambican economy lost a total of 3.6 per cent growth in 2020 and that total employment was 1.9 per cent down compared to a scenario without COVID-19. The main part of this loss is foreign-instigated, resulting from a demand reduction for Mozambican products by the rest of the world. The most heavily affected economic sectors are trade and accommodation and mining. Furthermore, our simulation implies that the production factors of capital and urban labour are more affected than rural labour. Moreover, the multisector multiplier analysis brings out the high dependence of Mozambique on a small number of export items (including tourism). Accordingly, Mozambique should promote economic diversification and explore the potential of reducing Mozambique's vulnerability to foreign shocks.
Keywords: E01; E16; E17; O21; 330; COVID-19; multisector multiplier analysis; social accounting matrix; Mozambique